Association study between D2 receptor A-241G, rs1799978 genetic variation and olanzapine efficacy in Iraqi schizophrenic patients - Zahra Jawd Mohammed Ali Al-Musawi; Atheer Majid Rashid Al-Juhaishi (Pharmacia, 2024)
This study aimed to assess the role of D2 receptor A-241G (rs1799978) genetic polymorphism and olanzapine response and safety in Iraqi schizophrenic patients. The case-control study composed of 100 schizophrenic patients consisting of both genders were recruited from the Psychiatry Outpatient Department and 50 apparently healthy volunteers, served as a control group. Patient response to olanzapine was evaluated with the aiding of the PANSS and genotyping of D2 receptor A-241G (rs1799978) polymorphisms was detected using the nested PCR method. The heterozygous (AG) and mutant (GG) alleles of D2 receptor A-241G (rs1799978) were significantly predominated in schizophrenic patients and absent in healthy volunteers. Schizophrenic patients with the G allele of D2 receptor A-241G (rs1799978) and who were administered olanzapine exhibited a notable resistance to olanzapine. In conclusion, the genetic polymorphism of D2 receptor A-241G (rs1799978) was significantly associated with resistance to olanzapine in Iraqi schizophrenic patients.